Мішень чи випадкова жертва " Великого терору"? - Бажан, О.; Золотарьов, В. (Краєзнавство, 2018)
У статті на основі маловідомих архівних документів робиться спроба відтворити біографію та діяльність в органах ВЧК-ДПУ-НКВС Валентина Сергійовича Шумова. The mass repressions that took place in the second half of the 1930-ies for strengthening the political regime affected all, without any exception, the social strata and ethnic groups that lived in the country of the Soviets. «Former kulaks», «members of anti-Soviet parties», «participants of insurgent organizations, fascist terrorist and espionage-sabotage counter-revolutionary formations», persons conducting «anti-Soviet activities » were doomed to be arrested. Numerous leading figures of the party, Soviet, economic bodies, representatives of the command-political staff of the Red Army and even the executors of the «great terror» – members of the NKVD bodies were caught under the power of the Stalinist punitive machine. They received the standard set of accusations of those days of «Yezovshchina»: betrayal to the Motherland, sabotage, espionage. However, among 1231 repressed employees of the NKVD of the Ukrainian SSR in 1937–1938, a significant proportion belongs to the so-called «violators of socialist legality», who were prosecuted for unlawful arrests, torture of prisoners, falsification of cases, etc. (Article 206 of the Criminal Code of the Ukrainian SSR). In the course of studying the life of the NKVD employees, who were convicted solely of «violating socialist legality», the authors of this article came across a criminal case of the former chief of the NKVD Cherkasy district department Yefim Naumovich Khavin, more famous in the Cheka circles as Valentyn Serhiyovych Shumov. A single case when an employee of the state security agency was «exposed in operational inactivity», was accused of «collapse of operational work», but was convicted of violating socialist legality. On unknown and little-known documents there was made an attempt in the article to find out whether V. Shumov (Khavin) was a conscious «saboteur» of mass repressions of 1937–1938, or was he the victim of his own official negligence. В статье на основании малоизвестных документов предпринята воссоздать биографии деяльность в органах ВЧК-ГПУ-НКВД Валентина Сергеевича Шумова.